Come Landfall : A Novel - Hoffman, Roy (Book collections on Project MUSE., 2014)
Set along the Mississippi Gulf Coast, the stories of three women and the men they love come together in this novel of war and hurricanes, loss and renewal. The worlds of three women and the men they love come together in this novel of war and hurricanes, loss and renewal. Christiane, or Nana, reliving the past in her eighties, her granddaughter Angela, working at a Biloxi casino in her twenties, and their teenage friend Cam, the daughter of a Vietnamese shrimper, form a deep connection. As they face heartbreak, their bonds nurture and sustain them. Ordinary people impacted by the s.